(untitled) (Bangladesh Journal of Agriculture, 2025)
An experiment was conducted at the experimental field of Sher-e-Bangla Agricultural University, Dhaka during January to June 2018 to evaluate the influence of planting method and leaf clipping on the yield performance of white maize. The experiment was laid out in a split plot design with three replications. The experiment comprised of two factors. Factor A: Planting method - 2 types [P1 = Sowing, P2 = Transplanting] and Factor B: Leaf clipping - 4 levels [C1 = no leaf clipping, C2 = all leaf clipping, C3 = clipping of fourleaves above cob, C4 = clipping of fourleaves belowcob]. White Maize Yungnuo 3000 was used for the experiment. Significant difference was observed on growth, yield and yield contributing parameters. In the case of planting method, all growth and yield attributes were showed better performance in treatment P1 than treatment P2. In the case of leaf clipping, C1 treatment performed best on the plant height (89.31, 168.32 and 217.21 cm, respectively) at different days after planting, leaf length (41.87 cm), cob length (19.77 cm), cob breadth (18.42 cm), number of row cob-1 (14.67), number of grain row-1 (34.65), grain yield (8.69 t ha-1), 100 seed weight (28.47 g), oven dried shell weight (17.87 g) and oven dried chaff weight (10.88 g), whereas poor performance was found in C2. In case of interaction, P1C1 treatment gave the highest performance in all aspect of growth and yield parameters and lowest found from P2C2. Bangladesh J. Agri. 2024, 49(2): 125-135